Coral Reef Restoration Techniques and Management Strategies in the Caribbean and Western Atlantic: A Quantitative Literature Review - Leah Hodges; Pamela Hallock (Diversity)
A quantitative literature review of restoration techniques and supporting management strategies used throughout the Caribbean and Western Atlantic from 1998 through 2024 was compiled using references from the Web of Science to highlight those with potential for reef replenishment. From 93 sources listed, 74 publications were relevant and categorized into subtopics based on the most prevalent restoration techniques. Roughly half the studies focused on three general topics: the benefits of restoring Acropora species, studies utilizing micro-fragmentation and fragment nurseries, and outplanting techniques. Other subtopics, each with at least three references, included optimizing substrates and artificial reefs, enhancing larval recruitment, emphasizing the role of herbivory, improving management practices, and addressing the impacts of tourism and community engagement. The information from the references was compiled to determine the overlap among categories and the ways in which techniques and management strategies might be applied simultaneously to enhance restoration outcomes. Additionally, sources were analyzed according to time and location of publication to better visualize the emergence of this area of research and restoration efforts. An increase in publications was observed from 2014 to 2024, associated with the rise in major events impacting coral reefs. The major locations for published research were the Florida reef tract and Puerto Rico, though restoration studies were also reported from the Bahamas and sites around the Caribbean. Criteria to assess the success of techniques included coral survival, recruitment, coral coverage, habitat structure and complexity, and biomass of marine life, including fish and invertebrates that inhabited a restored reef. Most restoration efforts utilized either fragmentation or assisted sexual breeding, followed by cultivation in nurseries or labs. Outplanting success depended on fragment size, attachment style, and site selection, with less-intrusive techniques and intermediate planting densities promoting survival. Tools like GAO maps can guide site selection based on herbivore presence and algal coverage. Monitoring is critical to ensuring coral survival, especially after the first year of outplanting, while community involvement can foster public engagement in reef conservation.